2020
DOI: 10.22541/au.160157379.92719550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A review of the genome, epidemiology, clinical features, prevention and treatment scenario of COVID-19: Bangladesh aspects

Abstract: Background: The ongoing acute respiratory disease pandemic termed COVID-19 caused by a newly emerged coronavirus has jeopardized the world's health and economic sectors. As of July 20, 2020, the virus now known as SARS-CoV-2 has already infected more than 14 million individuals and killed 612,815 patients with a mortality rate of 4.12% around the world regardless of age, gender and race.Main body: Bangladesh has become one of its worst sufferers, with 207,453 infected people and 2,668 related deaths with a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…After publication of the original article [ 1 ], the authors identified an error in the author’s name of Sohel Rana.…”
mentioning
confidence: 99%
“…After publication of the original article [ 1 ], the authors identified an error in the author’s name of Sohel Rana.…”
mentioning
confidence: 99%